ADDRESSING FORMS IN ENGLISH AND KARAKALPAK - Zhawgasharova, Amina Alawaddinovna (SCIENCE and SOCIETY, 2026)
This article examines forms of address in both English and Karakalpak and explores their functions in the process of communication. Differences between these forms are illustrated using examples drawn from the literature.
Keywords: address forms; gender and social status; politeness; linguoculturology; comparative analysis